Use of Direct Oral Anticoagulants in Patients With Antiphospholipid Syndrome: A Systematic Review and Comparison of the International Guidelines - Pastori, Daniele; Menichelli, Danilo; Cammisotto, Vittoria; Pignatelli, Pasquale (Frontiers in Cardiovascular Medicine, 2021)
Antiphospholipid antibody syndrome (APS) requires long-term anticoagulation to prevent recurrent thrombosis. Direct oral anticoagulants (DOACs) have been increasingly used in APS patients, but contradictory guidelines recommendations on their use do exist. We performed a systematic review of literature including studies investigating the role of DOACs in APS patients. At this aim, PubMed and Cochrane databases were searched according to PRISMA guidelines. We identified 14 studies which investigated the use of DOACs in patients with APS, of which 3 randomized clinical trials (RCTs), 1 post-hoc analysis of 3 RCTs, 7 case series and 3 cohort studies (2 prospective and 1 retrospective). Among DOACs, rivaroxaban was the most used (n = 531), followed by dabigatran (n = 90) and apixaban (n = 46). Regarding guidelines indications, the 2019 European Society of Cardiology (ESC) and American Society of Hematology (ASH) guidelines recommend against the use of DOACs in all APS patients. The European League Against Rheumatism (EULAR), British Society for Haematology (BSH), and International Society on Thrombosis and Haemostasis (ISTH) guidance provided more detailed indications stating that warfarin should be the first-choice treatment but DOACs may be considered in patients (1) already on a stable anticoagulation with a DOAC, (2) with low-quality anticoagulation by warfarin, (3) unwilling/unable to undergo INR monitoring, (4) with contraindications or serious adverse events under warfarin. Patients with arterial APS or triple positivity should be treated with warfarin while venous APS with single or double positivity may be candidate to DOACs, but high-quality studies are needed.